БҮЛБИЛЗИБАН ШАЙЫР - Бекбергенова, З.У (SCIENCE and SOCIETY, 2025)
The article analyzes the ideological, genre, and figurative aspects of Ajiniyaz poet’s poetry. In addition, there will be a detailed discussion about the lions in which the issues of nationality and gender equality are discussed.